Probing Metal Ion Discrimination in a Protein Designed to Bind Uranyl Cation With Femtomolar Affinity - Hoarau, Marie; Koebke, Karl J.; Chen, Zhan; Marsh, E. Neil G. (Frontiers in Molecular Biosciences, 2019)
The design of metal-binding sites in proteins that combine high affinity with high selectivity for the desired metal ion remains a challenging goal. Recently, a protein designed to display femtomolar affinity for UO22+, dubbed “Super Uranyl-binding Protein” (SUP), was described, with potential applications for removing UO22+ in water. Although it discriminated most metal ions present in seawater, the protein showed a surprisingly high affinity for Cu2+ ions. Here, we have investigated Cu2+ binding to SUP using a combination of electron paramagnetic resonance, fluorescence and circular dichroism spectroscopies. Our results provide evidence for two Cu2+ binding sites on SUP that are distinct from the UO22+ binding site, but one of which interferes with UO22+ binding. They further suggest that in solution the protein’s secondary structure changes significantly in response to binding UO22+; in contrast, the crystal structures of the apo- and holo-protein are almost superimposable. These results provide insights for further improving the selectivity of SUP for UO22+, paving the way towards protein-based biomaterials for decontamination and/or recovery of uranium.